Peran Transparansi dan Akurasi terhadap Pengungkapan Skandal Korupsi PT ANTAM Tbk - Lutvie Novita Zalwa; Milasiti Nursadiyah; Zahwa Nur Hasya; Ida Farida Adi Prawira (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The corruption case at PT ANTAM Tbk reflects weaknesses in transparency and accuracy within corporate management and the supervisory system in Indonesia. This study aims to analyze the role of transparency and accuracy in uncovering the corruption scandal at PT ANTAM Tbk, the corruption schemes involved, and their impact on public and investor trust. The research employs a qualitative approach using a case study analysis based on secondary data from financial reports, news articles, and legal documents. The findings reveal that financial report manipulation and ineffective supervision contributed to corrupt practices. Moreover, governance transparency failures have eroded stakeholder trust, negatively affecting business stability and investments. Therefore, reforms in corporate transparency and accuracy systems are crucial steps to prevent similar cases in the future. Keywords: Accuracy, Corruption, Transparency. The corruption case at PT ANTAM Tbk reflects weaknesses in transparency and accuracy within corporate management and the supervisory system in Indonesia. This study aims to analyze the role of transparency and accuracy in uncovering the corruption scandal at PT ANTAM Tbk, the corruption schemes involved, and their impact on public and investor trust. The research employs a qualitative approach using a case study analysis based on secondary data from financial reports, news articles, and legal documents. The findings reveal that financial report manipulation and ineffective supervision contributed to corrupt practices. Moreover, governance transparency failures have eroded stakeholder trust, negatively affecting business stability and investments. Therefore, reforms in corporate transparency and accuracy systems are crucial steps to prevent similar cases in the future.